Some aspects of western hemlock air permeability - Rayirath, Prasad; Avramidis, Stavros (Maderas. Ciencia y Tecnología, 2025)
Knowledge of the variability of fluid permeability of wood in general and of western hemlock in particular is of significant importance to the primary and secondary wood products processing industry of coastal British Columbia. For the purpose of this study, ten hemlock trees were randomly selected and specimens were prepared from three tree heights from each tree, namely, 1, 4 and 7 m. The air permeability of sapwood and heartwood in the longitudinal direction was measured using a dynamic method. Tracheid lengths were also obtained with a fiber quality analyzer and densities were measured by water displacement. The effect of tree height, tracheid length and density on the specific permeability of gross wood was then evaluated. The data revealed that height within the range measured has no effect on longitudinal permeability on heartwood whereas in sapwood the longitudinal permeability increases above 4 m of tree height. It was also found that longitudinal permeability was not significantly influenced by the tracheid length and wood density.